The first Sri Lankan species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) - Li, Ning; Yin, Zi-Wei (Zootaxa, 2020)
The genus Labomimus Sharp is represented by 44 species widely distributed in Asia, yet no species have been recorded from Sri Lanka. In the present paper, the first Sri Lankan species, L. srilankensis Li & Yin, sp. nov., is described and illustrated.